Time poverty and food production of women farmers: Case of Imbulpe DS division in Sri Lanka - Rathnachandra, S.D.D.; Malkanthi, S.H.P. (University of Jaffna, 2021)
Gender equity has been emphasized as a considerable aspect regarding sustainable development in any nation of the world. Thus, this study was conducted to assess the level of time poverty of women farmers and its impact for food production in the Imbulpe Divisional Secretariat (DS) division in Rathnapura district in Sri Lanka. The objectives were to identify the time allocation of women farmers and to assess the time poverty and the effect of time poverty on food production in the study area. A sample of 300 women farmers was randomly selected through the simple random sampling method from five selected Grama Niladhari (GN) divisions of the Imbulpe DS division. A self-administered questionnaire survey was used with the help of a pre-tested questionnaire, in data collection from April to July 2019. The model of Harvey and Mukhopadhyay (2007) was used as the measurement of time poverty with necessary modifications based on the situation of the study area. Descriptive statistics and regression analysis were used in data analysis. The findings revealed that the respondents have obtained a considerably high headcount index of time poverty (0.79) in their efforts in food production. Therefore, it can be concluded that women farmers who live in the Imbulpe area consist of a low level of time for their farming and leisure activities. Therefore, conducting extension programs related to the application of modern farming technologies and enhance market information accessibility to reduce the time consume when marketing their agricultural products and enhance the participation in stress management programs are timely important activities to help these women farmers.
Keywords: Farming activities; Food production; Gender equity; Time poverty; Women farmers